Limage Corporative des Institutions de Microfinance de DeuxiE8;me CatE9;gorie : Une Analyse de Six AntE9;cE9;dents Par l approche PLS (Global Journal of Management and Business Research, 2022)
This research mainly aims at highlighting a model linked to the antecedents of the corporate image of second-class microfinance institutions due to its emergence Six main dimensions of these antecedents service offer quality service cost contact staff physical environment customer knowledge and customer orientation are all put to test after literature review Data collected from 947 customers in 40 microfinance institutions and the Partial Least Squares method are used to test the conceptual model Findings show that it is possible to set up an antecedents consequences model of the corporate image In addition the conceptual framework of the corporate image s antecedents is enriched by two latent variables customer orientation and customer knowledge Despite some limitations this investigation presents some future research avenues